EDUCATION ON THE ROLE OF PARENTS REGARDING ADOLESCENT REPRODUCTIVE HEALTH - Yessy Syahradesi Br Tambunan; Yusnika Damayanti; Sri Mala Hayati; Ade Kartika; Arif Irpan Tanjung (EZRA SCIENCE BULLETIN, 2024)
Adolescence is a transition period from child to adult, where teenagers will experience puberty, namely physical and psychological changes. Therefore, the role of parents is very necessary regarding adolescent reproductive health to prevent and protect themselves from sexual behavior risks. This writing aims to increase knowledge of the role of parents regarding reproductive health. The education provided includes education about adolescent reproductive health and adolescent strategies for sexual behavior risk. The method used a 60-minute (lecture, question and answer session). Measurements were carried out using a questionnaire on the level of knowledge about reproductive health which was measured before and after providing education which consists of 20 questions. The sample for this service was 30 parents of teenagers at the Kaya Pangur Village Hall, Deleng District, Southeast Aceh Regency. The measurement results were analyzed using statistical tests, namely the Paired t-Test. The results showed that there was a difference in parents' knowledge scores about reproductive health before and after being given education about reproductive health (p-value = 0.000; α <0.05). Education about the role of parents regarding adolescent reproductive health plays a very important role for parents in knowing the progress of their adolescent child's development. Apart from that, the role of parents also plays a role in shaping the behavior of their children, especially health behavior related to reproductive health.